Vliv typu růstového faktoru na fenotyp subpopulací a kinetiku CD34+ bunek v periferní krvi a stepech periferních kmenových bunek pacientů s non-hodgkinskými lymfomy indikovaných k autologní transplantaci krvetvorby - Klabusay, M; Lysák, D; Hrabcáková, V; Navrátil, M; Coupek, P; Mayer, J (Casopis lekaru ceskych, 2008)
BACKGROUND: Peripheral blood stem cells are the preferred source for transplantation of hematopoiesis in patients with non-Hodgkin's lymphoma. Application of hematopoietic growth factors is a part of the mobilization chemotherapy regimen. Time overlap of the highest leukocyte and CD34+ cell count is required for optimal graft collection. Authors analyzed the effect of two growth factors (leridistim and filgrastim) on the kinetics and phenotype of CD34+ cells in patients with non-Hodgkin's lymphoma indicated for autologous peripheral blood stem cell transplantation. METHODS AND RESULTS: Authors analyzed phenotype of CD34+ cell subpopulations and their kinetics in peripheral blood and leukapheresis products by flow cytometry during mobilization and graft collection. Statistically significant differences in expression of lineage-committed antigens between growth factors were found (CD3, CD5--T-lineage, CD56 NK-lineage, CD20 for B-lineage, p < 0.05), as well as for lineage non-specific antigens (CD38, p < 0.05 and CD54, p < 0.01). The most significant divergence was observed between CD34+CD19+ subpopulations of leridistim and filgrastim stimulated blood and graft (p < 0.001). CONCLUSIONS: Expression of lineage-committed antigens on CD34+ subpopulations between two growth factors was statistically different. Kinetics of CD34+ cells during mobilization regimen with leridistim was not superior to filgrastim concerning the quality of graft.
Keywords: interleukin-3; Peripheral Blood Stem Cell Transplantation; filgrastim; nehodgkinský lymfom; Humans; Recombinant Fusion Proteins; lidé středního věku; Leukocytes; Antigens, CD34; Female; leukaferéza; dospělí; imunofenotypizace; lidé; Interleukin-3; Recombinant Proteins; antigeny CD34; Lymphoma, Non-Hodgkin; Leukapheresis; faktor stimulující kolonie granulocytů; mobilizace hematopoetických kmenových buněk; Adult; Stem Cells; rekombinantní proteiny; Immunophenotyping; ženské pohlaví; Male; Middle Aged; rekombinantní fúzní proteiny; Filgrastim; Granulocyte Colony-Stimulating Factor; kmenové buňky; mužské pohlaví; Hematopoietic Stem Cell Mobilization; transplantace periferních kmenových buněk; leukocyty